Investigating the Effect of Cutting Parameters of Ti–6Al–4V on Surface Roughness Based on a SPH Cutting Model - Niu, Weilong; Mo, Rong; Chang, Zhiyong; Wan, Neng (Applied sciences, 2019)
This work establishes a 2D numerical model to simulate the cutting process of workpieces made of Ti–6Al–4V, by applying an improved Smoothed Particle Hydrodynamics algorithm together with a modified constitutive model based on the Johnson–Cook model known as Hyperbolic Tangent (TANH). The location information of the surface particles obtained by the SPH cutting model are used to evaluate the variation trend of surface roughness with different parameters. Parameters that affect the surface roughness are investigated in detail by using the Taguchi method and the SPH cutting model. The present work provides an efficient and cost-effective approach to determine the optimal parameters for cutting processes for Ti–6AL–4V workpieces, through computer simulations in virtual environments, instead of expensive and time-consuming cutting experiments using actual workpieces.